Determination of antibiotics sensitivity profiles of bacteria isolated from raw milk - Talukder, Mukta; Ahmed, HM Manir (Asian Journal of Medical and Biological Research, 2016)
The extensive progress of dairy sectors in a developing country like Bangladesh, led to widespread use of antibiotics to improve the health and productivity of animals. Prolonged usage may lead to antibiotic residues in foods of animal origin; hence, the emergence of antimicrobial resistant microorganisms. Accurate data on the antibiotic usage in livestock treatment, antibiotic residues and antimicrobial resistances in raw milk in Bangladesh are lacking. This study aimed to investigate the types and usages of antibiotics in cattle, their potential microbial resistances in raw milk samples. To do so, a total of 54 raw milk samples were evaluated and the bacterial isolates were identified and measured for resistance to 4 antibiotics most commonly used during bacterial infection Bangladesh. Amongst all 54 (100%) isolates were positive to S. aureus and 36 (66.67%) isolates were positive to E coli. Determination of the antibiotic resistance pattern of isolates showed that all isolates of S. aureus were resistant to cefoxitin (81.48%), ampicillin (64.81%), ciprofloxacin (51.85%), and gentamycin (70.37%). E. coli showed resistance to cefoxitin (69.44%), ampicillin (83.33%), ciprofloxacin (77.78%), and gentamycin (86.11%). However multidrug resistance pattern was also found. The obtained results provide evidence that antimicrobial resistant strains of the above pathogens have become remarkably widespread in raw milk. This requires better management for antibiotic usages among livestock farmers to control sources of food contamination and reduce the health risks associated with the development of resistant microbial strains Asian J. Med. Biol. Res. September 2016, 2(3): 396-401